The Small Ethylene Response Factor ERF96 is Involved in the Regulation of the Abscisic Acid Response in Arabidopsis - Wang, Xiaoping; Liu, Shanda; Tian, Hainan; Wang, Shucai; Chen, Jin-Gui (Frontiers in Plant Science, 2015)
Ethylene regulates many aspects of plant growth and development including seed germination, leaf senescence, and fruit ripening, and of plant responses to environmental stimuli including both biotic and abiotic stresses. Ethylene Response Factors (ERFs) are plant-specific transcription factors and are a subfamily of the AP2 (APETALA2)/ERF transcription factor family. The function of many members in this large gene family remains largely unknown. ERF96, a member of the Group IX ERF family transcription factors, has recently been shown to be a transcriptional activator that is involved in plant defense response in Arabidopsis. Here we provide evidence that ERF96 is a positive regulator of abscisic acid (ABA) responses. Bioinformatics analysis indicated that there are a total four small ERFs in Arabidopsis including ERF95, ERF96, ERF97 and ERF98, and that ERF96 forms a cluster with ERF95 and ERF97. By using quantitative RT-PCR, we found that ERF96 is expressed in all tissues and organs examined except roots, with relatively high expression in flowers and seeds. Results from the protoplast transfection assay results indicated that the EDLL motif-containing C-terminal domain is responsible for ERF96’s transcriptional activity. Although loss-of-function mutant of ERF96 was morphologically similar to wild type plants, transgenic plants overexpressing ERF96 had smaller rosette size and were delayed in flowering time. In ABA sensitivity assays, we found that ERF96 overexpression plants were hypersensitive to ABA in terms of ABA inhibition of seed germination, early seedling development and root elongation. Consistent with these observations, elevated transcript levels of some ABA-responsive genes including RD29A, ABI5, ABF3, ABF4, P5CS and COR15A were observed in the transgenic plants in the presence of ABA. However, in the absence of ABA treatment, the transcript levels of these ABA-responsive genes remained largely unchanged. Our experiments also showed that water loss in ERF96 overexpression plants was slower than that in Col wild type plants. Stomatal closure assays indicated that ERF96 overexpression plants had reduced stomatal aperture in the presence of ABA. Taken together, our results suggest that AtERF96 positively regulates ABA responses in Arabidopsis.